Transformational Leadership and Teachers’ Organizational Commitment: The Mediating Role of Autonomy and Intelligence - Κοκκινίδης Ευστάθιος; Βάσιου Αικατερίνη; Βελώνη Μαλαματή; Ιορδανίδης Γεώργιος (Education Sciences, 2025)
Considering the imperative need to adapt leadership approaches according to the rapidly changing conditions of modern organizations, this study focuses on investigating the relationship between transformational leadership and teachers' organizational commitment in the light of work autonomy and emotional intelligence. According to the findings of the study, there is not statistically significant relationship between transformational leadership and organizational commitment. However, there is a significant indirect positive effect through work autonomy, which emerges as a key predictor of teachers' commitment. On the contrary, emotional intelligence is positively related to transformational leadership but shows a limited mediating role in this relationship. These findings highlight the importance of work autonomy as a fundamental factor in maximizing the effectiveness of transformational leadership, as well as the role of emotional intelligence regarding the development and promotion of a positive climate of collaboration. In conclusion, this research suggests the implementation of reforms aimed at strengthening teachers' work autonomy and enhancing emotional intelligence abilities, contributing to the proper functioning of organizations.